2005
DOI: 10.1021/ja054366t
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Isoniazid Resistance and Superoxide Reactivity in Mycobacterium tuberculosis KatG

Abstract: Isoniazid is an antituberculosis prodrug that requires activation by the catalase-peroxidase (KatG) of Mycobacterium tuberculosis. The activated species, presumed to be an isonicotinoyl radical, couples to NADH forming an isoniazid-NADH adduct that ultimately confers antitubercular activity. We have compared the catalytic properties of three KatGs associated with isoniazid resistance (resistance mutation KatGs, (RM)KatGs: R104L, H108Q, S315T) to wild-type enzyme and two additional lab mutations (wild-type phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
93
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 78 publications
(221 reference statements)
11
93
2
Order By: Relevance
“…Reports of INH activation in mixtures lacking an external oxidant (4,5,6,9,12,14,15) initially suggested that the peroxidatic process may not be required, but the mixtures of INH, NADH, and KatG would have supported NADH reduction of molecular oxygen to superoxide and low levels of H 2 O 2 (15) to activate the peroxidase reaction.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of INH activation in mixtures lacking an external oxidant (4,5,6,9,12,14,15) initially suggested that the peroxidatic process may not be required, but the mixtures of INH, NADH, and KatG would have supported NADH reduction of molecular oxygen to superoxide and low levels of H 2 O 2 (15) to activate the peroxidase reaction.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
“…Despite the considerable evidence that a peroxidatic process is involved in IN⅐NAD synthesis, attempts to rationalize the reaction entirely in terms of the peroxidatic pathway generally produced models that were incomplete from the standpoint of electron balance (5,7,10) or that involved hypothetical intermediates not characterized in any other system (5, 6). For example, a common scheme shows the isonicotinyl radical, generated in a peroxidatic reaction, reacting with NAD ϩ to yield IN⅐NAD, when such a reaction would actually yield the IN⅐NAD ϩ ⅐ radical (Fig.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
See 1 more Smart Citation
“…It claims over two million lives worldwide each year and dwells, hidden, in as many as two billion people (1). It is estimated that between 2005 and 2020, one billion people will be newly infected, over 125 million people will get sick, and 30 million will die of TB if control is not further strengthened (2). The worsening situation has prompted the World Health Organization to declare TB a global public health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that additionally, phenyl oxygen (Oη) of Y218 and amide nitrogen (N) backbone of M244 in the covalent adduct have hydrogen (H)-bonds with the guanisyl N 1 and N 2 of Arg409 (R409), respectively (Yamada et al, 2002). The covalent adduct has been shown to be generated by autocatalytic process (Ghiladi et al, 2005a). Crystallographic analysis of KatG from Bulkhorderia pseudomallei (Bp) has indicated that the side-chain of R409 (corresponding to HmKatG numbering) shows conformational change depending on both of pH and the physicochemical state of the active site (Carpena et al, 2005 M244L] in BpKatG considerably decreased the catalase activity, whereas the peroxidase activity was even enhanced (Regelsberger et al, 2000;Jakopitsch et al, 2004;Singh et al, 2004 Y218F] in the M244-Y218-W95 covalent adducts induced complete loss of the catalase activity, whereas the peroxidase activity was highly enhanced in Sy KatG (Jakopitsch et al, 2003a;Jakopitsch,et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%